Aspirated Consonants in Malay Dialects of Peninsular Malaysia: A Survey in Baling, Kedah (Jurnal Bahasa, 2024)
Aspiration is a foreign linguistic feature in Peninsular Malaysia. However, there are exceptions to this statement. This is because a small part of the local dialects spoken in the northern part of Peninsular Malaysia, especially along the Malaysia-Thailand border, apparently contains aspiration features in their phonological system. Among the Malayic dialects in Peninsular Malaysia that contain this feature is the Baling Malay dialect. Based on a review of previous studies, the main factor that created this feature in the Baling Malay dialect is linguistic contact. Therefore, pure dialects actually have no aspiration. For instance, the Baling Malay dialect received this feature after contact with the Siamese language. In this paper, the contact that created this feature of aspiration is discussed in detail from social and historical perspectives. In addition, this paper presents a discussion that links the widespread diffusion of aspiration in the Baling Malay dialect with internal linguistic innovation mechanisms, particularly the process of syllable shortening and analogy. The paper concludes with the possibility that the consistency of aspiration in the Baling Malay dialect may be eroded by two factors. The first is the geopolitical boundaries that limited contact with the Siamese language. The second is the high intensity of contact with the Kedah Malay dialect due to geopolitical boundaries that likely revived voiceless stop consonants without any exhalation element as a characteristic marker of aspiration. The findings of this study confirm the need to integrate internal and external linguistic elements in order to accurately explain the geographical and historical distribution of dialects, ensuring that any theory derived from this integration is adequate.Keywords: Aspirated consonant, aspiration, Malayic, Baling Malay dialect, contact, analogyFull Text: PDF